Free recombination within Helicobacter pylori - Suerbaum, Sebastian (The National Academy of Sciences, 1998)
Sequences of three gene fragments (flaA, flaB, and vacA) from Helicobacter pylori strains isolated from patients in Germany, Canada, and South Africa were analyzed for diversity and for linkage equilibrium by using the Homoplasy Test and compatibility matrices. Horizontal genetic exchange in H. pylori is so frequent that different loci and polymorphisms within each locus are all at linkage equilibrium. These results indicate that H. pylori is panmictic. Comparisons with sequences from Escherichia coli, Neisseria meningitidis, and Drosophila melanogaster showed that recombination in H. pylori was much more frequent than in other species. In contrast, when multiple family members infected with H. pylori were investigated, some strains were indistinguishable at all three loci. Thus, H. pylori is clonal over short time periods after natural transmission.